PENGARUH MOTIVASI KERJA, BEBAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KOTA SEMARANG - Alia Ariyanti; Muhamad Nukha Murtadlo (STKIP Pesisir Selatan, 2026)
This study focuses on analyzing the effects of work motivation, workload, and organizational culture on employee performance. The issue addressed in this study is the indication of declining public satisfaction with services or employee performance, as evidenced by the number of public complaints and the decline in the Public Satisfaction Index (PSI). This research employs a quantitative approach using a causal-associative research design. The population consists of all employees of the Semarang City Education Department, with a saturated sampling technique yielding 120 respondents. Data collection was conducted via a questionnaire using a Likert scale and analyzed using SPSS version 30. The findings of this study indicate that (1) Partially, work motivation has no effect on employee performance, as indicated by a Sig value of 0.165; (2) Partially, workload has a positive and significant effect on employee performance, as indicated by a Sig value of 0.22 (3) Partially, organizational culture has a positive and significant influence, as indicated by a Sig value <0.001; (4) Simultaneously or collectively, the three variables in the study have a positive and significant influence on employee performance, as evidenced by a Sig value <0.001.